Supported Decision Making in Serious Mental Illness. Issue 1 (2nd January 2018) - Jeste, Dilip V.; Eglit, Graham M. L.; Palmer, Barton W.; Martinis, Jonathan G.; Blanck, Peter; Saks, Elyn R.
Abstract : Objective : Making decisions is central to the exercise of control over one's well-being. Many individuals with serious mental illness (SMI) experience limitations in their decision-making capacity. These individuals have often been placed under legal guardianship and substitute decision makers have been appointed to make decisions on their behalf. More recently, supported decision making (SDM) has emerged as a possible alternative in some cases. SDM involves recruitment of trusted supports to enhance an individual's capacity in the decision-making process, enabling him or her to retain autonomy in life decisions. This overview examines issues associated with decision-making capacity in SMI, frameworks of substitute decision making and SDM, and emerging empirical research on SDM. Method : This is an overview of the medical and legal literature on decision making capacity and supported decision making for persons with SMI. Results : Many but not all individuals with SMI exhibit decrements in decision-making capacity and skill, in part due to cognitive impairment. There are no published data on rates of substitute decision making/guardianship or SDM for SMI. Only three empirical studies have explored SDM in this population. These studies suggest that SDM is viewed as an acceptable and potentially superior alternative to substitute decision making for patients and their caretakers. Conclusions : SDM is a promising alternative to substitute decision making for persons with SMI. Further empirical research is needed to clarify candidates for SDM, decisions in need of support, selection of supporters, guidelines for the SDM process, integration of SDM with emerging technological platforms, and outcomes of SDM. Recommendations for implementation of and research on SDM for SMI are provided.